Cormorant predation in fyke net fishing: The direct effects of a protected bird on coastal commercial fishing - Westerbom, Mats; Ekblad, Camilla; Hopkins, Juhani; Laaksonen, Toni; Olin, Mikko; Ovaskainen, Antti; Jormalainen, Veijo (Elsevier BV, 2025)
The population size of great cormorants, Phalacrocorax carbo sinensis, has risen steeply in the Baltic Sea over the past 40 years. The growing population has resulted in polarized conflicts between conservation and coastal fisheries due to the losses cormorants may inflict on fisheries. Mitigation of the conflicts requires objective estimates of true losses to fisheries, but quantitative research on losses has been scarce. We used continuous video-recordings to systematically quantify cormorant visits and their activity at 15 fyke nets during the 2022–2023 breeding and post breeding seasons. More than 2400 h of video footage were recorded, in which cormorants were found for 664 h. We also quantified the frequency of fish injured by birds in coastal fishing catches using data from the EU Fisheries Data Collection Program including data from fyke nets and gill nets. Our results show that cormorants frequently foraged in open, floating fyke nets but relatively rarely in submerged nets, leading to significantly higher losses in the former. Monitoring data from fyke and gill net catches covering the entire Finnish coast revealed that the proportion of bird-injured fish in catches is very modest (0.5 %) but can be considerable in individual catches. Finally, results indicate that cormorant visits and the proportion of injured fish in the catch tend to increase when distance to the nearest cormorant colony decreases. We conclude that the losses caused by birds are generally modest, except in open fyke nets where cormorants may conduct hundreds of dives and catch dozens of fish a day. Our study shows that cormorant depredation is highly variable in time and space, but also partly manageable by selecting gear that conforms to local cormorant pressures. We underline the importance of systematic scientific research when measuring damage caused by cormorants and ask for evidence-based political strategies to mitigate perceived cormorant problems.